2010
DOI: 10.1111/j.1365-2966.2010.17398.x
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter scaling relations in intermediate z haloes

Abstract: We investigate scaling relations between the dark matter (DM) halo model parameters for a sample of intermediate redshift early - type galaxies (ETGs) resorting to a combined analysis of Einstein radii and aperture velocity dispersions. Modeling the dark halo with a Navarro - Frenk - White profile and assuming a Salpeter initial mass function (IMF) to estimate stellar masses, we find that the column density ${\cal{S}}$ and the Newtonian acceleration within the halo characteristic radius $r_s$ and effective rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 42 publications
13
42
0
Order By: Relevance
“…Del found a correlation of the surface density with M200, in agreement with Napolitano et al (2010), Cardone & Tortora (2010), and Boyarsky et al (2009), but with a smaller scatter, and they also found a correlation between baryon column density and mass.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Del found a correlation of the surface density with M200, in agreement with Napolitano et al (2010), Cardone & Tortora (2010), and Boyarsky et al (2009), but with a smaller scatter, and they also found a correlation between baryon column density and mass.…”
Section: Introductionsupporting
confidence: 78%
“…Cardone & Tortora (2010), based on central velocity dispersion of local galaxies and strong lensing at intermediate redshift, have shown that the Newtonian acceleration and column density correlate with different quantities: the visual luminosity LV , the effective radius re, the stellar mass M * and the halo mass M200 in agreement with Boyarsky et al (2009) and in disagreement with the results of D09 and G09. Napolitano et al (2010) calculated < ρDM > re, which is proportional to the column density S, for a large sample of elliptical galaxies.…”
Section: Introductionmentioning
confidence: 67%
“…gravitational lensing (see, e.g. Cardone & Tortora 2010; Treu et al 2010) and studies of the central DM fraction in local ETGs (Napolitano et al 2011) suggest that observations are consistent more with a Salpeter rather than a Chabrier IMF for ETGs (unless some strong AC is considered). Moreover, it has also been suggested that the IMF might vary with luminosity (Renzini & Ciotti 1993; Tortora et al 2009) with a Salpeter one being generally preferred for brighter systems (as probed by the SLACS lenses).…”
Section: Testing the Sim Modelmentioning
confidence: 99%
“…The claimed correlation with mass seems almost insensitive to the adopted galaxy mass profile or initial mass function, IMF (e.g., Cardone et al 2009;Cardone & Tortora 2010;Cardone et al 2011), but it can become uncertain in case a non-ΛCDM scenario, with mass following the (non-homologous) light distribution, is adopted (e.g., Trujillo et al 2004;Tortora et al 2009Tortora et al , 2012. The scenario is even more complicated if one takes into account the effect of a non universal IMF (van Dokkum & Conroy 2010;Treu et al 2010;Thomas et al 2011;Conroy & van Dokkum 2012;Cappellari et al 2012Cappellari et al , 2013Spiniello et al 2012;Wegner et al 2012;Barnabè et al 2013;Dutton et al 2013;Ferreras et al 2013;Goudfrooij & Kruijssen 2013;La Barbera et al 2013;Tortora et al 2013;Weidner et al 2013;Goudfrooij & Kruijssen 2014;Shu et al 2015;McDermid et al 2014;Tortora et al 2014a,c;Martín-Navarro et al 2015;Spiniello et al 2015;Lyubenova et al 2016;Tortora et al 2016;Corsini et al 2017;Li et al 2017;Sonnenfeld et al 2017;Tortora et al 2017).…”
Section: Introductionmentioning
confidence: 99%